2011
DOI: 10.1177/0954406211429758
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic measurement of self-loosening in bolted joints

Abstract: Self-loosening of bolted joints in response to vibration can lead to the catastrophic failure of a range of engineering components and structures. Many techniques employed to study this phenomenon focus on directly measuring the preload remaining in the bolt itself, and offer little insight into the behaviour of the clamped interface. In this study, a non-intrusive ultrasonic reflection-based technique is used to first characterize interface pressure in the joint, and then determine the rate at which relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Ultrasonic techniques have also been used to study contact pressure distribution at the clamped interface of bolted joints [11,12]. It was further shown that ultrasonic reflections from the clamped interface could be used to estimate the progress of relaxation in bolted joints [13]. The ultrasonic method provides a better accuracy compared to the torque wrench, and also determines bolt tension without any impact on the joint stiffness, as opposed to strain gauges.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic techniques have also been used to study contact pressure distribution at the clamped interface of bolted joints [11,12]. It was further shown that ultrasonic reflections from the clamped interface could be used to estimate the progress of relaxation in bolted joints [13]. The ultrasonic method provides a better accuracy compared to the torque wrench, and also determines bolt tension without any impact on the joint stiffness, as opposed to strain gauges.…”
Section: Introductionmentioning
confidence: 99%
“…When the ultrasonic wavelength is long compared to the scale of the air gaps in the interface, the interface as a whole behaves like a reflector. Marshall et al use the reflection coefficient of the ultrasonic for measuring the contact pressure relaxation in bolted joints [25].…”
Section: Piezoelectric Active Sensing Methodsmentioning
confidence: 99%
“…Additional work was carried out by Dwyer-Joyce to further understand the relationship between surface roughness and stiffness [15], [16]. This work has been continued and numerous static ultrasonic contact measurements have been carried out using a scanning system to investigate machine element interfaces, such as Marshall et al [17], [18] investigating the contact between bolted plates, interference fits [19] and the static contact pressure and area between a sectioned railroad vehicle wheel and rail [20]. The technique involves pulsing an ultrasonic pressure wave towards the contact interface and deriving information from reflected signals.…”
Section: Measurement Of Contact Pressure and Areamentioning
confidence: 99%
“…By monitoring the phase and amplitude of the reflected wave, it is possible to understand a great deal about the host material and the interface. This technique has been successfully employed to measure contact pressure [3], [16], [17], [18], [19], [20], [21], [22], [23], but also lubricant film thickness [25], viscosity [26], and wear [27].…”
Section: Introductionmentioning
confidence: 99%